Transposon‐mediated glial cell line‐derived neurotrophic factor overexpression in human adipose tissue‐derived mesenchymal stromal cells: A potential approach for neuroregenerative medicine?. (12th March 2022) - Rasińska, Justyna; Klein, Charlotte; Stahn, Laura; Maidhof, Felix; Pfeffer, Anna; Schreyer, Stefanie; Gossen, Manfred; Kurtz, Andreas; Steiner, Barbara; Hemmati‐Sadeghi, Shabnam
Abstract: Glial cell line‐derived neurotrophic factor (GDNF) has neuroprotective effects and may be a promising candidate for regenerative strategies focusing on neurodegenerative diseases. As GDNF cannot cross the blood–brain barrier to potentially regenerate damaged brain areas, continuous in situ delivery with host cells is desired. Here, a non‐viral Sleeping Beauty transposon was used to achieve continuous in vitro overexpression of GDNF in immune‐privileged human adipose tissue‐derived mesenchymal stromal cells (GDNF‐tASCs). In addition, in vivo survival, tolerance, and effectiveness of transfected cells were tested in a very mild 6‐hydroxydopamine (6‐OHDA)‐induced dopamine depletion rat model by means of intrastriatal injection on a sample basis up to 6 months after treatment. GDNF‐tASCs showed vast in vitro gene overexpression up to 13 weeks post‐transfection. In vivo, GDNF was detectable 4 days following transplantation, but no longer after 1 month, although adipose tissue‐derived mesenchymal stromal cells (ASCs) could be visualized histologically even after 6 months. Despite successful long‐term in vitro GDNF overexpression and its in vivo detection shortly after cell transplantation, the 6‐OHDA model was too mild to enable sufficient evaluation of in vivo disease improvement. Still, in vivo immunocompatibility could be further examined. ASCs initially induced a pronounced microglial accumulation at transplantation site, particularly prominent in GDNF‐tASCs. However, 6‐OHDA‐induced pro‐inflammatory immune response was attenuated by ASCs, although delayed in the GDNF‐tASCs group. To further test the therapeutic potential of the generated GDNF‐overexpressing cells in a disease‐related context, a follow‐up study using a more appropriate 6‐OHDA model is needed.